Climate Risk, Cooperation and the Co-Evolution of Culture and Institutions. Issue 637 (20th January 2021) - Buggle, Johannes C; Durante, Ruben
Abstract: This paper examines the relationship between economic risk and the evolution of social cooperation. We hypothesise that trust developed in pre-industrial times as a result of experiences of cooperation aimed at coping with climatic risk. We document that European regions with higher pre-industrial climatic variability display higher levels of trust today. This effect is driven by variability in the growing season months and is more pronounced in agricultural regions. Regarding possible mechanisms, our results indicate that climatic risk favoured intercommunity exchange and the early adoption of inclusive political institutions which is associated with higher quality of local governments today.